An exploratory study on strategic metal recovery of coal gangue and sustainable utilization potential of recovery residue. (15th March 2022) - Qin, Qizheng; Deng, Jiushuai; Geng, Huanhuan; Bai, Zhongyi; Gui, Xiahui; Ma, Zhitao; Miao, Zhenyong
Abstract: Coal gangue is a resource that is often improperly managed, especially during the current strategic metal element shortage. Achieving the efficient and green cooperative recovery of primary elements and strategic metal elements is critical, especially in the treatment without acid and alkali. In this study, the low-temperature combined roasting-DI water leaching method extracted valuable elements and prepared adsorption materials from coal gangue. The element migration and reaction mechanisms were investigated in detail. The results show that the primary reaction path includes the decomposition of ammonium sulfate into ammonium hydrogen sulfate, which reacts with kaolinite to form aluminum ammonium sulfate. Al, Fe, Ga, Li, Mg, Sr, Ti, and V were strongly correlated during roasting. The combined roasting of ammonium chloride and ammonium sulfate promoted the dissolution of Al and Li significantly. The specific surface area of water-leached gangue residue was adjusted by combined roasting, and its adsorption effect on lead ions was stronger than that of raw gangue and kaolinite. The present process presents an eco-friendly solution for the comprehensive utilisation of coal gangue. Graphical abstract: Image 1 Highlights: Combined ammonium salt roasting improves the metal leaching rate. The migration of various metals in the treatment was studied. The structure change from coal gangue was studied by ammonium salt roasting. Leaching residue is expected to be the adsorption material.